Implementación de mejora en los procesos operativos estandarizados de saneamiento en la planta extractora de la empresa Aceites Morichal S.A.S. (2024)
Based on the cleaning guide and disinfection of the ministry of the environment in which defines the importance that we must have for counteract the invasion of infectious agents, eliminating them with cleaning activities and disinfection through operational processes standardized sanitation standards, a practice in the company Aceites Morichal with the aim to make a proposal for improvement to the Processes Standardized Sanitation Operations (POES) in the extraction plant.